The Hindi Swear Words Used by Indians: A Descriptive Qualitative Study - Dharmasanti, Ni Made Utari; Budasi, I Gede; Ramendra, Dewa Putu (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This research aims to (1) identify swear words used by Indians, (2) analyze their forms, (3) examine their functions, and (4) explore their references. It employs a qualitative descriptive method and was conducted in Nusa Penida, Klungkung Regency, Bali. Data were collected through document analysis and interviews with three informants selected based on specific criteria. The researcher acted as the main instrument, supported by an analysis sheet and interview guides. The findings reveal a total of 33 Hindi swear words. In terms of form, 15 are monomorphemic, 12 polymorphemic, 3 noun phrases, and 3 independent clauses. Regarding function, 18 swear words are used to discredit others, 7 to provoke, and 8 to provide emotional catharsis. As for references, the words relate to sex activity (8), excrement (2), animals (4), personal background (4), bodily functions (8), and death (1). These results show that Hindi swear words are varied in structure, purpose, and reference, reflecting both the emotional intensity and cultural context in which they are used. This study enhances the understanding of Indian sociolinguistics by demonstrating how swearing serves not only as verbal aggression or expression, but also as a reflection of societal values, interpersonal dynamics, and cultural identity.